Same age
See explanation below
Step-by-step explanation:
Let the age of Jasmine = y
Multiplying Jasmine age by 3 and adding 6:
= (y × 3) + 6
= 3y + 6
Multiplyng the sum by 2:
2 × the sum = 2 × (3y + 6)
= 6y + 12
Let James age = z
Multiplying the age by 2 and adding 4:
James age × 2 = z × 2 = 2z
adding 4 = 2z + 4
Multiplying the sum y 3:
3 × the sum = 3 × (2z + 4)
= 6z + 12
Now since they are twins, they ae most likely same age
This means:
6y + 12 = 6z + 12
subtracting 12 from both sides:
6y = 6z
dividing both sides by 6:
y = z
Hence, Jasmine age is the same as James age
B) The expression for Jasmine = 2(3y + 6) = 6y + 12
The expression for James = 3(2z + 4) = 6z + 12
let the twin's age = 2, 3, 4, 5
when twin's age = 2
6y + 12 = 6(2) + 12 = 12 + 12 = 24
6z + 12 = 6(2) + 12 = 12 + 12 = 24
when twin's age = 3
6y + 12 = 6(3) + 12 = 18 + 12 = 30
6z + 12 = 6(3) + 12 = 18 + 12 = 30
when twin's age = 4
6y + 12 = 6(4) + 12 = 24 + 12 = 36
6z + 12 = 6(4) + 12 = 24 + 12 = 36
when twin's age = 5
6y + 12 = 6(5) + 12 = 30 + 12 = 42
6z + 12 = 6(5) + 12 = 30 + 12 = 42
Plotting the table: